General practitioners' opinion on early and pre‐dementia diagnosis of AD: A MOPEAD project survey in five European countries: Neuropsychiatry and behavioral neurology/Mild cognitive impairment/Early symptomatic disease. (7th December 2020) - Sannemann, Lena; Müller, Theresa; Waterink, Lisa; Zwan, Marissa D.; Wimo, Anders; Stomrud, Erik; Pino, Susana; Espinosa, Jordi Arrufat; Rodriguez‐Gomez, Octavio; Benaque, Alba; Bon, Jaka; Dron, Amanda; et al.
Abstract: Background: Over the last decade, research efforts have facilitated early detection of dementia and underlying diseases, such as Alzheimer disease (AD). There is growing evidence for the benefits of early diagnosis, including access to education, available treatment and support. On the other hand, the lack of a cure and the fear to stigmatize the patient are among the arguments that speak against early disclosure of a diagnosis. General Practitioners (GPs) are often the first contact person when cognitive changes arrive, and they play a key role in early identification of the disease. Based on the experiences working with GPs as part of the multinational "Models of Patient Engagement for Alzheimer's Disease" (MOPEAD) project, an EU‐funded public‐private study within the Innovative Medicines Initiative (IMI‐2) research agenda, we aimed to assess the current attitude of GPs towards early and pre‐dementia diagnosis for AD at the stage of mild cognitive impairment (MCI) or very mild dementia. Method: We designed a survey to measure the current attitude of GPs towards early and pre‐dementia diagnosis of AD at the MOPEAD sites in five European countries (Germany, Slovenia, Spain, Sweden, and the Netherlands). The questionnaire covered several topics, including attitude towards early diagnosis, diagnostic procedures, resources and opinion on present and future treatment options. Chi‐square tests were carried out to analyze differences among countries. Result: 343 GPs completed the survey. In total, 74% of GPs indicated that they considered an early diagnosis of value. However, only 44% of GPs felt confident in handling the diagnostic procedures for very early dementia and MCI. Currently available pharmacological treatments were mostly regarded as having low benefit, while 68% considered non‐pharmacological treatment options as "beneficial and not sufficiently available". There were country‐specific differences in the GPs' perception of monetary resources ( X 2 (4)=117.26, p < .001) and time ( X 2 (4)=14.84, p > .01) available for the patient. Conclusion: Our findings provide an up‐to‐date overview on GPs' opinion towards early and pre‐dementia diagnosis in five European countries. We show that the majority of GPs considers an early diagnosis beneficial, yet they are faced with country‐specific challenges that can contribute to delayed or missed diagnosis.